π-π stacking interactions: Non-negligible forces for stabilizing porous supramolecular frameworks - Deng, Ji-Hua (Sci Adv, 2020)
Revealing the contribution of π-π stacking interactions in supramolecular assembly is important for understanding the intrinsic nature of molecular assembly fundamentally. However, because they are much weaker than covalent bonds, π-π stacking interactions are usually ignored in the construction of porous materials. Obtaining stable porous materials that are only dependent on π-π stacking interactions, despite being very challenging, could address this concern. Here, we present a porous supramolecular framework (π-1) stabilized only by intermolecular π-π stacking interactions. π-1 shows good thermal and chemical stability not only in various organic solvents but also in aqueous solution in a broad pH range. Furthermore, featuring one-dimensional channels with dangling thiolate groups, π-1 exhibits excellent Hg(2+) removal performance, with adsorption capacity as high as 786.67 mg g(−1) and an adsorption ratio as high as 99.998%. In addition, π-1 also shows high adsorption selectivity to Hg(2+) in the presence of a series of interfering ions.